2010
DOI: 10.1242/jcs.070631
|View full text |Cite
|
Sign up to set email alerts
|

Growth arrest in human T-cells is controlled by the non-coding RNA growth-arrest-specific transcript 5 (GAS5)

Abstract: There was an error published in J. Cell Sci. 121, 939-946.The reverse primer sequence for RT-PCR in the Materials and Methods is given in the 3¢-to-5¢ direction, not the 5¢-to-3¢ direction as stated. The correct sequence of the reverse primer is 5¢-TCTTGTGCCATGAGACTCCATCAG-3¢.The authors apologise for this error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 0 publications
6
34
0
Order By: Relevance
“…It was reported working as a tumor suppressor to sensitize cells to apoptosis [88][89][90]. Overexpression of GAS5 led to increased apoptosis and slower cell cycle [91]. Kino et al found that GAS5 was upregulated during growth arrest induced by serum starvation or the lack of growth factors.…”
Section: Other Lncrnasmentioning
confidence: 99%
“…It was reported working as a tumor suppressor to sensitize cells to apoptosis [88][89][90]. Overexpression of GAS5 led to increased apoptosis and slower cell cycle [91]. Kino et al found that GAS5 was upregulated during growth arrest induced by serum starvation or the lack of growth factors.…”
Section: Other Lncrnasmentioning
confidence: 99%
“…Gas5 is present in all tissue types and is one of the most highly expressed non-coding RNAs in the human genome 17 . Gas5 has been implicated in many important cellular and physiological processes including p53 signaling 7 , embryogenesis 6 , growth arrest and cell cycle 18,19 , and apoptosis 14,20-22 . In addition, Gas5 is required for rapamycin action in immune cells 20 , and Gas5 knockdown affects mRNA levels for M-Ras, prion protein (PrP), parkin, and other genes 6 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, human C/D box snoRNAs specifically expressed in the brain have been implicated in the interference with A-to-I editing (Vitali et al, 2005) and in the regulation of alternative mRNA splicing of the serotonin receptor (Kishore and Stamm, 2006). The human non-coding growth arrestspecific transcript 5 (GAS5), which encodes ten different snoRNAs in its introns (U44, U47, U74, U75, U76, U77, U78, U79, U80, U81; Smith and Steitz, 1998), was shown to play a critical role in the control of cell growth and apoptosis, to be down regulated in breast cancer (Mourtada-Maarabouni et al, 2009), and has evoked as a candidate gene in the development of autoimmune disease (Mourtada- Maarabouni et al, 2008). Together with the recent demonstration of tumor suppressor characteristics in the human snoRNA U50 (Dong et al, 2008), these observations suggest that snoRNA genes may be involved in controlling oncogenesis and sensitivity to therapy in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…As a first outcome, we report here the results of our quest of U79-related fly snoRNAs. Human U79 is responsible for methylation of 28S at a site highly conserved in metazoans, but unmodified in yeast, and represents one out of ten snoRNAs encoded by the GAS5 pro-apoptotic ncRNA involved in cell growth, cancer and autoimmune diseases (Smith and Steitz, 1998;Nakamura et al, 2008;Mourtada-Maarabouni et al, 2008, 2009). This search led to the identification of two novel snoRNAs with peculiar genomic arrangement, one of which was antisense to eiger (egr), a Drosophila regulatory gene encoding a Tumor Necrosis Factor-like ligand involved in the regulation of cell differentiation, death and immunity (Igaki et al, 2002;Kauppila et al, 2003;Schneider et al, 2007).…”
Section: Introductionmentioning
confidence: 99%